Effect of Drug Use Stigma to Accessing Harm Reduction Services by People Who Inject Drugs in Nairobi County - Mukami, Evangeline Ndwiga; Muiruri, Lillian; Kimemia, Fredrick (International Journal of Health Sciences, 2025)
Purpose: This study aims to explore the influence of drug use stigma on Harm Reduction Services (HRS) accessibility for People Who Inject Drugs (PWIDs) in Nairobi County.​ It seeks to understand the various barriers encountered by PWIDs, particularly those related to stigma, that prevent them from accessing essential services like syringe service programs. Methodology: Adopting the Health Belief Model (HBM), this study utilized a cross-sectional research survey design. The target population was 1100 PWIDs in Starehe sub-county, as highlighted by the Kenya HIV/AIDS Indicator Survey of 2019. A sample size of 285 participants was determined using the Fischer sample determination formula, and participants were selected through the snowball technique. Findings: A significant majority of respondents, 77.8% (n = 221), reported experiencing stigma due to their drug use, with most experiencing it monthly (34.9%) or weekly (28.2%), indicating a regular pattern. Mobile services were the most utilized HRS delivery model (30.3%, n=86), followed by peer outreach (28.2%, n=80). A considerable proportion (40.1%, n=114) reported moderate challenges in HRS accessibility. Stigma was identified as a pervasive barrier for PWIDs across all stages of drug use, originating from both social (family, friends, and community) and institutional (healthcare providers, law enforcement) domains. Unique Contribution to Theory, Policy and Practice: This study shows that stigma significantly hinders PWIDs’ access to harm reduction services within the Health Belief Model. It calls for decriminalization, anti-discrimination laws, and expansion of OST and SCS. Practically, it urges participatory advocacy and inclusive outreach to reduce stigma and improve service accessibility for marginalized populations.